2015
DOI: 10.1039/c4cc09087j
|View full text |Cite
|
Sign up to set email alerts
|

Thyminate(2−)-bridged cyclic tetranuclear rhodium(iii) complexes formed by a template of a sodium, calcium or lanthanoid ion

Abstract: In the thyminate(2-)-bridged tetranuclear Cp*Rh(III) complexes incorporating a Na(+), Ca(2+) or Ln(3+) cation, homochiral aggregation of four Rh(III) centres was achieved to form metallacalix[4]arene-type clusters. The thyminate(2-) bridged two Rh(III) and the third metal ion with a μ3-1κN(1):2κ(2)N(3),O(2):3κO(2) mode in the Na(+) and Ca(2+) complexes, while in the Ln(3+) analogues it exhibited a different bridging mode, μ3-1κN(1):2κ(2)N(3),O(4):3κO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…The ion detected with m/z 395 is either a three‐coordinate Pt II complex, or a four‐coordinate compound with 1MeU chelating the metal via N3 and one of its two exocyclic O4 or O2 oxygen atoms. In general, N,O chelation of pyrimidine nucleobases is not observed in solid state structures of Pt II complexes as a consequence of unfavorable bonding angles within such a chelate, but there are (rare) cases of N,O chelates for Pd II , [26] or – less uncommon – for octahedral metal ions, e. g., Cp * Rh III [27] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion detected with m/z 395 is either a three‐coordinate Pt II complex, or a four‐coordinate compound with 1MeU chelating the metal via N3 and one of its two exocyclic O4 or O2 oxygen atoms. In general, N,O chelation of pyrimidine nucleobases is not observed in solid state structures of Pt II complexes as a consequence of unfavorable bonding angles within such a chelate, but there are (rare) cases of N,O chelates for Pd II , [26] or – less uncommon – for octahedral metal ions, e. g., Cp * Rh III [27] …”
Section: Resultsmentioning
confidence: 99%
“…In general, N,O chelation of pyrimidine nucleobases is not observed in solid state structures of Pt II complexes as a consequence of unfavorable bonding angles within such a chelate, but there are (rare) cases of N,O chelates for Pd II , [26] or -less uncommon -for octahedral metal ions, e. g., Cp*Rh III . [27] The weak signal at m/z 412 is assigned to the Na + adduct of 1 a, hence to {Na[Pt(NH 3 ) 2 (1MeU)Cl]} + (not shown). Also, an ion resulting from a loss of chloride, hence [Pt(NH 3 ) 2 (1MeU)] + (with m/z 354), is observed, yet not pointing to the presence of any of the other species detected following reaction of 1 a with AgNO 3 (see below).…”
Section: Esi-mass Spectra Of 1 Amentioning
confidence: 99%
“…[14] The reactions were carried out with a range of alkynes, in methanol, at room temperature, and led to the M-C alkyne insertion products (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) in good to excellent yields, regardless the nature of the metal [Ir III or Rh III ]. [14] The reactions were carried out with a range of alkynes, in methanol, at room temperature, and led to the M-C alkyne insertion products (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) in good to excellent yields, regardless the nature of the metal [Ir III or Rh III ].…”
Section: Rh III and Ir Iii Derivativesmentioning
confidence: 99%
“…[26,27] In this regard, nucleobases are ideal building blocks for the construction of supramolecular structures with metal ions, as they provide several potential donor sites and an inherent ability to secondary interactions resulting from hydrogen bonding and/or π-π stacking. [28][29][30][31][32] For example, Olmstead and Fish showed that in situ generated [RhCp*(H 2 O) 3 ](OTf ) 2 was able to react with 9-methyladenine and adenosine in D 2 O at pH 7.1 affording trimeric structures (64). [11,26] Most of the structures reported are based on direct coordination of the nucleobase binding sites with diverse metal ions.…”
Section: Cage Structuresmentioning
confidence: 99%
See 1 more Smart Citation